Peningkatan Motivasi dan Kemampuan Menulis Puisi Melalui Teknik Timlo Aplikasi Copy The Master Peserta Didik Kelas VIII A SMP N 3 Sragi Kabupaten Pekalongan - Margiati Margiati (TRANSFORMATIKA, 2017)
This researcher was motivated to conduct this study because of the less ability of the leaener to write poetry. It coud be seen from the average score of the pretest of poetry writing which only reached 73. The purpose of the study was to improve motivation and the learning result of poetry writing in the students of VIIIA of SMPN 3 Sragi, Pekalongan by applying Timlo aplication of Copy the Master Technique. The method used in this Class Action Research was using two cycles. The subjects were 32 students of class VIII A. The result showed that there was a significant improvement in learning the technique of poetry wriring. The average score of pretest was 73. After the applying Timlo technique, the average score of the cycle I was 79.88 and it increased in the cycle II to 84.00. The increasing score from the pretest to the first cycle was 68.8%. Meanwhile, the increasing score from cycle I to cycle II was 41.2%. In addition, there was an increasing motivation of the students for learning to poetry writing. Thus, it was suggested for Indonesian subject’s teacher for using this model in teching and learning process.Keywords: motivation, learning outcomes, writing poetry, timlo engineering, copy the master